Roflumilast partially reverses smoke-induced mucociliary dysfunction - Schmid, Andreas (Respir Res, 2015)
BACKGROUND: Phosphodiesterases (PDEs) break down cAMP, thereby regulating intracellular cAMP concentrations and diffusion. Since PDE4 predominates in airway epithelial cells, PDE4 inhibitors can stimulate Cystic Fibrosis Transmembrane Conductance Regulator (CFTR) by increasing cAMP. Tobacco smoking and COPD are associated with decreased CFTR function and impaired mucociliary clearance (MCC). However, the effects of the PDE4 inhibitor roflumilast on smoke-induced mucociliary dysfunction have not been fully explored. METHODS: Primary normal human bronchial epithelial cells (NHBE) from non-smokers, cultured at the air-liquid interface (ALI) were used for most experiments. Cultures were exposed to cigarette smoke in a Vitrocell VC-10 smoking robot. To evaluate the effect of roflumilast on intracellular cAMP concentrations, fluorescence resonance energy transfer (FRET) between CFP- and YFP-tagged protein kinase A (PKA) subunits was recorded. Airway surface liquid (ASL) was measured using light refraction scanning and ciliary beat frequency (CBF) employing infrared differential interference contrast microscopy. Chloride conductance was measured in Ussing chambers and CFTR expression was quantified with qPCR. RESULTS: While treatment with 100 nM roflumilast had little effect alone, it increased intracellular cAMP upon stimulation with forskolin and albuterol in cultures exposed to cigarette smoke and in control conditions. cAMP baselines were lower in smoke-exposed cells. Roflumilast prolonged cAMP increases in smoke-exposed and control cultures. Smoke-induced reduction in functional, albuterol-mediated chloride conductance through CFTR was improved by roflumilast. ASL volumes also increased in smoke-exposed cultures in the presence of roflumilast while it did not in its absence. Cigarette smoke exposure decreased CBF, an effect rescued with roflumilast, particularly when used together with the long-acting ß-mimetic formoterol. Roflumilast also enhanced forskolin-induced CBF stimulation in ASL volume supplemented smoked and control cells, confirming the direct stimulatory effect of rising cAMP on ciliary function. In active smokers, CFTR mRNA expression was increased compared to non-smokers and ex-smokers. Roflumilast also increased CFTR mRNA levels in cigarette-smoke exposed cell cultures. CONCLUSIONS: Our results show that roflumilast can rescue smoke-induced mucociliary dysfunction by reversing decreased CFTR activity, augmenting ASL volume, and stimulating CBF, the latter particularly in combination with formoterol. As expected, CFTR mRNA expression was not indicative of apical CFTR function.